Efficacy and safety of daily mirabegron 50 mg in male patients with overactive bladder: a critical analysis of five phase III studies. (June 2017) - Tubaro, Andrea; Batista, José E.; Nitti, Victor W.; Herschorn, Sender; Chapple, Christopher R.; Blauwet, Mary Beth; Siddiqui, Emad; Huang, Moses; Oelke, Matthias
Background: Oral pharmacotherapies to treat overactive bladder (OAB) are used less in men despite a similar prevalence of storage symptoms as women. The efficacy and safety of once-daily mirabegron 50 mg was evaluated in male OAB patients from five phase III studies that included placebo or antimuscarinic (tolterodine ER 4 mg or solifenacin 5 mg) as a comparator. Methods: Three pooled 12-week placebo-controlled studies (mirabegron 50 mg versus placebo) and one 12-week non-inferiority phase IIIb study (BEYOND; mirabegron 50 mg versus solifenacin 5 mg) were used for efficacy (daily micturition frequency, urgency and incontinence episodes) and safety analyses. An additional 52-week active-controlled phase III safety study (mirabegron 50 mg versus tolterodine ER 4 mg) was included in the safety analysis. Male patients aged ⩾18 years with OAB for ⩾3 months were included in the analyses. Patients may also have a history of lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH)/benign prostatic enlargement (BPE) or concomitant use of α1 -blockers. Results: In the pooled studies, mirabegron 50 mg demonstrated superiority versus placebo (treatment difference: −0.37 [95% confidence interval (CI): −0.74, −0.01]) for reducing micturition frequency; improvements in urgency and incontinence were not significantly different between mirabegron 50 mg and placebo. In BEYOND, mirabegron 50 mg was comparable with solifenacin 5 mg for reducing micturition frequency, urgency, and incontinence episodes. Mirabegron was well tolerated at 12 and 52 weeks and overall treatment-emergent adverse events (AEs) were similar to those with placebo. Conclusions: In a male OAB population with or without LUTS associated with BPH/BPE, mirabegron 50 mg provided similar improvements in urgency, frequency, and incontinence as solifenacin 5 mg, and is a well-tolerated alternative to antimuscarinics. In the three pooled 12-week studies, significant differences were not seen for urgency and incontinence versus placebo, although mirabegron 50 mg did demonstrate significant improvements versus placebo for frequency.